Cholinergic reflex control of inflammation: mechanistic and translational advances in transcutaneous auricular vagus nerve stimulation across rheumatic, metabolic, and postoperative disorders - Han, Rui; Peng, Zongbo; Zhuo, Ming; Song, Yuanyuan; Liu, Yuhao; Zhang, Xiaowen; Deng, Zihao; Xia, Lingyi; Zhong, Mao-Lin (Frontiers in Immunology, 2026)
Transcutaneous auricular vagus nerve stimulation (taVNS) has recently emerged as a focal noninvasive neuromodulatory approach in anti-inflammatory therapeutics. The vagus nerve functions as a critical neuroimmune interface, tonically suppressing proinflammatory cytokine release via the cholinergic anti-inflammatory pathway (CAP). This mechanism provides substantial therapeutic potential across a spectrum of inflammatory disorders, including postoperative systemic inflammation. Clinical trials have demonstrated the anti-inflammatory efficacy of taVNS, supporting its expanded use in rheumatoid arthritis, systemic lupus erythematosus, gout, inflammatory bowel disease (IBD), and other immune-mediated disorders. Investigations into postoperative inflammation and metabolic syndrome are now emerging. In this review, we synthesize the anatomical substrate, mechanistic framework, and disease-specific applications of taVNS, with a particular emphasis on how stimulation parameters influence therapeutic outcomes. Finally, we outline current challenges and propose future directions to advance research and clinical translation.